Amyloid precursor protein in human breast cancer: An androgen‐induced gene associated with cell proliferation. Issue 11 (26th August 2013) - Takagi, Kiyoshi; Ito, Shigehiro; Miyazaki, Toshiaki; Miki, Yasuhiro; Shibahara, Yukiko; Ishida, Takanori; Watanabe, Mika; Inoue, Satoshi; Sasano, Hironobu; Suzuki, Takashi
Abstract : Amyloid precursor protein (APP) is a transmembrane protein that is highly expressed in brain tissue. Recently, APP has been implicated in some human malignancies, and its regulation by androgens has also been demonstrated. Such findings suggest the importance of APP in hormone‐dependent breast carcinoma, but APP has not yet been examined in breast carcinoma tissues. Therefore, in this study, we examined the biological and clinical significance of APP in breast carcinoma using immunohistochemistry and in vitro studies. APP immunoreactivity was detected in 57 out of 117 (49%) breast carcinoma tissues examined, and it was positively associated with androgen receptor (AR) expression. APP immunoreactivity was also significantly associated with Ki‐67 LI and increased risk of recurrence in the estrogen receptor (ER)‐positive cases, and was an independent prognostic factor in these patients. Subsequent in vitro experiments demonstrated that APP mRNA expression was significantly induced by biologically active androgen dihydrotestosterone in both a dose‐dependent and a time‐dependent manner in MCF‐7 breast carcinoma cells, which was potently suppressed by an AR blocker hydroxyflutamide. Moreover, cell proliferation activity of MCF‐7 and MDA‐MB‐231 cells was significantly associated with their APP expression level. These findings suggest that APP is an androgen‐induced gene that promotes proliferation activity of breast carcinoma cells. Moreover, APP immunohistochemical status is considered a potent prognostic factor in ER‐positive breast cancer patients.